Vestibular System Evaluation: Results on Analysis of Vestibulony stagmography (VNG)) - Mitra Janghorban; Amir Tayebi-Sani; Sadegh Ja'far-Zadeh; Ebrahim Pishyareh (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: Falls are one of the major problems in the elderly and are considered one of the "Geriatric Giants". Recurrent falls an important cause of morbidity and mortality in this segment of the population and is a marker of poor physical and cognitive status. The aim of the present study is to compare the VNG (Videonystagmography) test results in adults with and without falls history. Materials & Methods: 60 adults ( 30 with one or more falls history and 30 without any falls history) above 65 year old performed the VNG subtests included saccade, gaze, smooth pursuit, positional nystagmus, spontaneous nystagmus and caloric at rehabilitation faculty of Tehran University of Medical Sciences. Results: According to the data 74% of the faller group showed abnormal performance in the caloric subtest and more than 60% had abnormal results in the saccade, gaze and smooth pursuit subtests too. The members who suffered from central vestibular disorders had worse function than the others who suffered from peripheral vestibular ones. Conclusion: The non- faller group had better performance than the faller group in all of the subtests which indicates better vestibular system status in this group. According to the results, VNG performance can help guide the clinicians in the development of a safe exercise program.